Determinants of Horizontal and Vertical Intra-Industry Trade of Indonesian Manufacturing with ASEAN-4 - Moh. Adenan; Lilis Yuliati; Aisiyah Andini Rahmasari; Thomas Soseco; Agus Sumanto (Jurnal Ekonomi dan Studi Pembangunan, 2024)
Intra-industry trade between Indonesia and some neighbouring countries like the Philippines, Malaysia, Thailand, and Vietnam can be characterised as an imperfectly competitive market and be driven by increasing returns to achieve economies of scale. This research investigates the dynamics of Indonesia's intra-industrial trade in the manufacturing industry with ASEAN-4 countries, namely the Philippines, Malaysia, Thailand, and Vietnam, from 2005 to 2021. The independent variables used are the difference in Gross Domestic Product (GDP), real exchange rate, and Foreign Direct Investment (FDI). We also estimate the Grubel-Lloyd Index and decompose the intra-industry trade either dominated by vertical or horizontal intra-industry trade. The data is then analysed by the panel data method. Our findings show that intra-industry trade taking place in the region has a strong level dominated by vertical intra-industry trade, resulting in goods traded of different quality. Next, the variable of difference in GDP has a significant negative effect on intra-industry trade, the variable of the real exchange rate has a significant positive impact, and FDI has a positive and not significant effect.